2022
DOI: 10.1038/s41598-022-18246-0
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic acid B inhibits RAW264.7 cell polarization towards the M1 phenotype by inhibiting NF-κB and Akt/mTOR pathway activation

Abstract: M1 macrophages secrete a large number of proinflammatory factors and promote the expansion of atherosclerotic plaques and processes. Salvianolic acid B (Sal B) exerts anti-inflammatory, antitumor and other effects, but no study has addressed whether Sal B can regulate the polarization of macrophages to exert these anti-atherosclerotic effects. Therefore, we investigated the inhibition of Sal B in M1 macrophage polarization and the underlying mechanism. The effects of different treatments on cell viability, gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Previous literature has reported that Sal B inhibits M1 macrophage polarization by suppressing NF-κB pathway activation and reducing Akt/mTOR activation [ 22 ]. In this paper, we revealed the potential mechanism by which Sal B inhibits macrophages trend toward M1 type from the perspective of the regulation of glycolysis and histone lactylation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has reported that Sal B inhibits M1 macrophage polarization by suppressing NF-κB pathway activation and reducing Akt/mTOR activation [ 22 ]. In this paper, we revealed the potential mechanism by which Sal B inhibits macrophages trend toward M1 type from the perspective of the regulation of glycolysis and histone lactylation.…”
Section: Discussionmentioning
confidence: 99%
“…Its increased expression induces NF‐κB p65 translocation into the nucleus, promoting the transcription of proinflammatory factors IL‐6, IL‐1β, and TNF‐α. Furthermore, activation of NF‐κB and AKT/mTOR pathways results in the M1 phenotype polarization of RAW264.7 macrophages (Zou et al., 2022). Therefore, the quantitative expression of proinflammatory factors can determine the degree of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Pharmacology frontiersin.org the LPS + IFN-γ-activated AKT/mTOR pathway and enhanced autophagy, while insulin activation of the mTOR signaling pathway counteracted the inhibitory effect of Sal B on M1 macrophage polarization, suggesting that Sal B can inhibit M1 macrophage polarization and reduce the release of inflammatory factors through the mTOR signaling pathway, thus exerting an anti-atherogenic effect (Zou et al, 2022). Tanshinone I and Tanshinone IIA are also important active substances extracted from Salvia miltiorrhiza Bunge.…”
Section: Othersmentioning
confidence: 99%